Post-influenza aspergillus ventriculitis - Canning, Benjamin; Senanayake, Varuni; Burns, Daniel; Moran, Edward; Dedicoat, Martin (Clinical infection in practice, 2020)
Invasive aspergillosis is a complication of influenza infection, usually in the form of invasive pulmonary aspergillosis and more often seen in the context of immunosuppression. Post-influenza central nervous system invasion by aspergillus is very rarely described in the literature. We report a 63-year old male, with a background of rheumatoid arthritis managed with methotrexate, who initially presented with a respiratory infection. He was positive for Influenza A H1N1 by a reverse-transcriptase polymerase chain reaction assay from a throat swab. He subsequently developed a progressive neurological impairment, had cranial imaging consistent with ventriculitis and hydrocephalus, and a lymphocytic cerebrospinal was obtained by lumbar puncture. Imaging of his chest revealed cavitatory lung disease and a possible aspergilloma. Following an endoscopic third ventriculostomy, cerebrospinal fluid microscopy revealed fungal hyphae and aspergillus DNA was detected by a polymerase chain reaction assay. Despite appropriate anti-fungal treatment the patient died of complications from an aspergillus ventriculitis. Clinicians should remain vigilant for post-influenza aspergillosis, even in patients only minimally immunocompromised. Post-influenza aspergillus infection of the central nervous system, presumably by a haematogenous route, is rarely described but does occur as demonstrated by this case. •Invasive aspergillus infection is a recognised complication of influenza•Aspergillosis of the central nervous system is a rare complication of influenza•Aspergillus infection has characteristic radiological findings•The mainstay of treatment is with an azole but evidence is poor